Whole Exome Sequencing Identifies Three Novel Mutations in the ASPM Gene From Saudi Families Leading to Primary Microcephaly - Muhammad Imran Naseer; Muhammad Imran Naseer; Angham Abdulrahman Abdulkareem; Angham Abdulrahman Abdulkareem; Osama Yousef Muthaffar; Sameera Sogaty; Hiba Alkhatabi; Hiba Alkhatabi; Sarah Almaghrabi; Sarah Almaghrabi; Adeel G. Chaudhary; Adeel G. Chaudhary; et al. (Frontiers Media S.A., 2021)
Autosomal recessive primary microcephaly (MCPH) is a neurodevelopmental defect that is characterized by reduced head circumference at birth along with non-progressive intellectual disability. Till date, 25 genes related to MCPH have been reported so far in humans. The ASPM (abnormal spindle-like, microcephaly-associated) gene is among the most frequently mutated MCPH gene. We studied three different families having primary microcephaly from different regions of Saudi Arabia. Whole exome sequencing (WES) and Sanger sequencing were done to identify the genetic defect. Collectively, three novel variants were identified in the ASPM gene from three different primary microcephaly families. Family 1, showed a deletion mutation leading to a frameshift mutation c.1003del. (p.Val335*) in exon 3 of the ASPM gene and family 2, also showed deletion mutation leading to frameshift mutation c.1047del (p.Gln349Hisfs*18), while in family 3, we identified a missense mutation c.5623A>G leading to a change in protein (p.Lys1875Glu) in exon 18 of the ASPM gene underlying the disorder. The identified respective mutations were ruled out in 100 healthy control samples. In conclusion, we found three novel mutations in the ASPM gene in Saudi families that will help to establish a disease database for specified mutations in Saudi population and will further help to identify strategies to tackle primary microcephaly in the kingdom.